Calibration of the design wind load and snow load considering the historical climate statistics and climate change effects. (November 2021) - Hong, H.P.; Tang, Q.; Yang, S.C.; Cui, X.Z.; Cannon, A.J.; Lounis, Z.; Irwin, P.
Highlights: Updated probabilistic models for the annual maximum wind speed and the ground snow load depth for Canada. Treated thunderstorm and non-thunderstorm winds in reliability analysis separately. Calibrated new design wind and snow load and load combination factors for Canadian practice. Calibrated and recommended load scaling factors accounting for climate change effects for the National Building Code of Canada. Abstract: In the present study, an updating of the probabilistic models used for calibrating the wind load, snow load and companion load factors for the National Building Code of Canada (NBCC) are presented. The update of probabilistic models for the extreme wind speed and ground snow depth is based on historical climatological data over Canadian sites. For the updating of the statistics of the extreme wind speed, the effect of mixed wind climate (i.e., thunderstorm winds and non-thunderstorm winds) is considered. Reliability analysis is carried out based on this update by considering different load combinations. The results indicate that, for an improved reliability consistency, the use of a high return period to specify the environmental loads and with a unit load factor is preferable to the use of 50 year return period and a load factor greater than one for structural design code making, if the coefficient of variation of the extreme climatological elements is spatially varying. Most importantly, based on these findings and the results from the climate change modelling results, sets of load scaling factors accounting for climate change effects are calibrated for different regions in Canada. Both the use of the target reliability index for a 50-year design working life as well as of the target minimum required annual reliability index within each of the 50-year design working life are considered for the reliability-based calibration. Specific recommendations on the load and companion load factors are suggested for a future edition of NBCC.